Current Research Status of Allelopathy - AHMAD JUNAEDI; MUHAMMAD AHMAD CHOZIN; KWANG HO KIM (Bogor Agricultural University, Indonesia, 2006)
The term of allelopathy refers to chemical interactions (inhibitory or stimulatory) between plants, between plants and microorganisms, and between microorganisms. The wealth of information on the processes, procedures, and practices of allelopathy has contributed to understanding this field of science. Recently, researches of allelopathy have been conducted in laboratory, greenhouse, and field with multifaceted standpoint in some concerning area: (i) allelochemicals identifications and screening test; (ii) ecological and physiological aspects of allelopathy; (iii) genetic studies and the possibilities of using plant breeding or genetic manipulation to enhance allelopathic varieties; (iv) the use of allelopathic potential in the biological control, including as natural pesticide, of weeds and plant diseases as eco-friendly approach for sustainable agriculture scheme. Key words: Allelochemicals, biological control, sustainable agriculture